Role of VEGF-VEGFR2 signaling pathway in psoriasis - Xiaomei LUO; Zhiyong CHENG; Xiaoqun HAN; Yong WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
VEGF-VEGFR2 signaling pathway plays an important role in the course of psoriasis. Binding of VEGF to VEGFR2 induces receptor dimerization and autophosphorylation at multiple tyrosine sites, promoting the activation of the downstream ERK1/2 signaling pathway. Phosphorylated ERK1/2 is highly expressed in keratinocytes in psoriatic lesions, while VEGFR2 activation induces ERK1/2 phosphorylation and upregulates the expression of keratin K6, K16, and K17. At the same time, the activation of ERK1/2 can enhance inflammatory response and vascular proliferation. Therefore, blockade of VEGF-mediated vegF-VEGFR2 signaling pathway can regulate the expression of downstream genes in VEGF-VEGFR2 signaling pathway. VEGF and VEGFR2, the key molecules in VEGF-VEGFR2 signaling pathway, may serve as potential therapeutic targets for psoriasis. VEGF inhibitors can block vegF-VEGFR2 signaling pathway by inhibiting VEGF or VEGFR2, playing a therapeutic role in psoriasis. In this review, we review the recent advances in the involvement of VEGF-VEGFR2 pathway in psoriasis.